English Learning Motivation of First-Year Students in Universiti Sultan Zainal Abidin (UniSZA) - Azilah Mahammed; Rafizah Mohd Rawian (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
Studies have shown that motivation influences the learning of English as a second language (ESL) where it has not only increased students’ drive in language learning but it also influenced their language performance. However, most of the first-year students in Universiti Sultan Zainal Abidin (UniSZA) were found to have low English performance. This study thus examined UniSZA students’ motivation level in learning English and significant difference in their level of motivation in learning English in terms of gender. The sample for this study comprised of 112 first-year students of UniSZA. The data for this study were gathered through the adapted version of Attitude/Motivation Test Battery (AMTB). The findings revealed that most of the students had high level of motivation and the difference between males and females in terms of their motivation level was significant. Interestingly, females were found to be more motivated than the males. It is hoped that the findings would help English instructors in their teaching as they can plan appropriate motivational strategies for both the male and female students to enhance their potential in learning English and thus increases their English performance.